Students' Response To The Application Of The Remap-Tgt (Reading Concept Map Team Game Tournament) Model On Human Digestive System Materials - Tasya Karima; Muhibbuddin Muhibbuddin; Andi Ulfa Tenri Pada; Samingan Samingan; Wiwit Artika (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
AbstractStudent responses are responses given during the learning process, the Remap-TGT model is a learning activity by combining reading activities to understand learning materials and build concept maps. The purpose of this study is to see the response of students in the Reading Remap-TGT learning activities on the material of the human digestive system. This study used the experimental method with the research subjects were 33 students of class XI MIPA 1. The parameters measured were student responses through student response questionnaires, the data were analyzed using the percentage formula. The results of the study were responses with very good categories. The conclusion from the research is that each indicator has a value with a very good category. The excellent response is evidence of the students' interest in the Remap-TGT learning model, which is very interesting and memorable.Keywords: student response, remap-tgt, human digestive systemAbstrakRespon peserta didik yaitu tanggapan yang diberikan selama proses pembelajaran, model Remap-TGT yaitu kegiatan pembelajaran dengan menggabungkan kegiatan membaca untuk memahami materi pembelajaran dan membangun peta konsep. Tujuan penelitian ini yaitu akan melihat respon peserta didik dalam kegiatan pembelajaran Reading Remap-TGT pada materi sistem pencernaan manusia. Penelitian ini menggunakan metode eksperimen  dengan subjek penelitian adalah 33 peserta didik kelas XI MIPA 1. Parameter yang diukur adalah respon peserta didik melalui angket respon peserta didik, data dianalisis dengan menggunakan rumus persentase.. Hasil penelitian yaitu respon dengan kategori sangat baik. Simpulan dari penelitian bahwa pada masing-masing indikator memiliki nilai dengan kategori sangat baik. Respon yang sangat baik merupakan bukti ketertarikan peserta didik terhadap model pembelajaran Remap-TGT sangat menarik dan berkesan.Kata Kunci: respon peserta didik, remap-tgt, sistem pencernaan manusia